2022
DOI: 10.1177/20101058221114743
|View full text |Cite
|
Sign up to set email alerts
|

Osimertinib 80 mg EOD? Does this work?

Abstract: Osimertinib is a third-generation thyroxine kinase inhibitor (TKI) used in treating advanced non-small cell lung cancer (NSCLC) patients with epidermal growth factor receptor (EGFR) mutation. Osimertinib is used as a second line treatment for patients who develop EGFR T790 M resistance mutation rather than first line due to financial constraints. We present a case of a 60-year-old Chinese gentleman who diagnosed as stage 4 adenocarcinoma with EGFR Exon 19 deletion. His disease progressed after a year of treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…To this end, some oncologists may opt for off-label practices, such as changing the frequency of taking long half-life drugs from daily to every other day. 45 Lowering the dose of the cancer drug is also a strategy to reduce the cost of cancer treatment. For osimertinib, a third-generation tyrosine kinase inhibitor used to treat metastatic non-small cell lung cancer patients with specific epidermal growth factor receptor ( EGFR ) mutations, for example, results of the AURA1 clinical trial showed that the response rates among patients with detectable EGFR mutation T790M was similar across all dose levels (20 mg, 40 mg, 80 mg, 160 mg, and 240 mg).…”
Section: Strategies For Improving Cancer Drug Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, some oncologists may opt for off-label practices, such as changing the frequency of taking long half-life drugs from daily to every other day. 45 Lowering the dose of the cancer drug is also a strategy to reduce the cost of cancer treatment. For osimertinib, a third-generation tyrosine kinase inhibitor used to treat metastatic non-small cell lung cancer patients with specific epidermal growth factor receptor ( EGFR ) mutations, for example, results of the AURA1 clinical trial showed that the response rates among patients with detectable EGFR mutation T790M was similar across all dose levels (20 mg, 40 mg, 80 mg, 160 mg, and 240 mg).…”
Section: Strategies For Improving Cancer Drug Accessmentioning
confidence: 99%
“… 46 Preliminary results from a small group of 29 patients in an ongoing clinical trial also showed that prescribing half the dose (40 mg instead of the conventional 80 mg) resulted in an acceptable response rate and median progression-free survival in the patients. 45 Thus, if positive results are obtained in future larger-scale trials, the cost of treatment with osimertinib may be reduced to half.…”
Section: Strategies For Improving Cancer Drug Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…A case report described a Chinese gentleman with metastatic lung adenocarcinoma with EGFR exon 19 deletion whose disease had progressed on afatinib, and whose blood EGFR T790M was negative. He received osimertinib 80 mg orally every other day, with a good partial response (PR) and a PFS of 9 months [ 20 ]. Based on the encouraging preclinical and early clinical data, we administered osimertinib 80 mg orally at a reduced frequency on a compassionate basis to patients with EGFR mutant lung cancer who were unable to afford full dose osimertinib, refused or had progressed on intravenous chemotherapy and did not have any other treatment options available.…”
Section: Introductionmentioning
confidence: 99%
“…A case report described a Chinese gentleman with metastatic lung adenocarcinoma with EGFR exon 19 deletion whose disease had progressed on afatinib, and whose blood EGFR T790M was negative. He received osimertinib 80 mg orally every other day, with a good partial response and a PFS of 9 months [29]. Based on the encouraging preclinical and early clinical data, we administered osimertinib 80 mg orally at a reduced frequency on a compassionate basis in patients with EGFR mutant lung cancer who were unable to afford full dose osimertinib, refused or had progressed on intravenous chemotherapy, and did not have any other treatment options available.…”
Section: Introductionmentioning
confidence: 99%